Resistance of Anopheles mosquitoes to insecticides in the Democratic Republic of the Congo: A literature review and future directions - Koto-Te-Nyiwa Ngbolua, Jean-Paul; Basosila, Narcisse; Mbembo, Blaise; Mukomena, Eric; Masengo, Colette Ashande; Fiacre, Agossa; Zanga, Josué; Ulrich, Seth; Nagahuedi, Jonas (Orapuh Journal, 2024)
Introduction Malaria remains one of the most prevalent and deadly parasitic infections in the Democratic Republic of the Congo (DRC), posing a significant public health challenge. Purpose This literature review aimed to investigate the resistance and sensitivity of Anopheles mosquitoes to insecticides used in the DRC. Methods A bibliographic search was conducted using search engines such as Google Scholar, ScienceDirect, PubMed, and Scopus with keywords including "resistant Anopheles," "insecticide resistance," and "susceptible Anopheles" specific to the DRC. Additional keywords such as "molecular target of insecticides," "modes of action of insecticides," and "mechanisms of insecticide resistance" were used without geographical restrictions. Articles were selected based on criteria including relevance to the subject, source reliability, and recency. Special emphasis was placed on studies with robust methodologies. To ensure comprehensiveness, diverse studies were included to provide a holistic overview of the subject. Results Numerous scientific articles and reports were selected for analysis. The findings indicate that Anopheles mosquitoes exhibit resistance to key pyrethroid insecticides (e.g., permethrin, deltamethrin, and alpha-cypermethrin) commonly used for treating long-lasting insecticidal nets (LLINs) and in indoor residual spraying (IRS). Evidence from primary and secondary sources suggests that insecticide resistance is spreading across regions and increasing, primarily due to the use of insecticides in agriculture. Of the 22 studies reviewed, 12 reported the restoration of Anopheles sensitivity to pyrethroid insecticides when synergist piperonyl butoxide (PBO) was used. Conclusions The findings of this review provide a valuable reference for policymakers and public health authorities working to design effective malaria control strategies in the DRC. The results highlight the current status of Anopheles insecticide resistance and the progress and challenges associated with malaria control efforts in the region. Further investigation into the use of nanoparticles (NPs) as complementary tools in malaria vector control is recommended, given their potential to target mosquitoes at various life stages and contribute to the eradication of the disease.